2022
DOI: 10.1186/s12936-022-04375-4
|View full text |Cite
|
Sign up to set email alerts
|

Human behaviour directs household-level exposure to malaria vectors in Bandarban, Bangladesh

Abstract: Background Bangladesh has reduced malaria incidence and mortality by over 75% between 2010 and 2020. Widespread long-lasting insecticidal net (LLIN) distribution and use is one of the measures responsible for this success. Recalcitrant malaria hotspots within the Chittagong Hill Tracts districts suggest important drivers of malaria risk may remain uncharacterized. Methods Towards understanding how household-level human behaviour impacts exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Routine night studying sessions predispose school-age children to mosquito bites since they do not use protective measures. Unfortunately, entomological studies have reported a substantial proportion of biting mosquitoes before midnight (24:00) [28][29][30][31]. The under-five may be protected against such risk as they would be at home and under bed nets early.…”
Section: Discussionmentioning
confidence: 99%
“…Routine night studying sessions predispose school-age children to mosquito bites since they do not use protective measures. Unfortunately, entomological studies have reported a substantial proportion of biting mosquitoes before midnight (24:00) [28][29][30][31]. The under-five may be protected against such risk as they would be at home and under bed nets early.…”
Section: Discussionmentioning
confidence: 99%
“…Routine night studying sessions predispose school-age children to mosquito bites since they do not use protective measures. Unfortunately, entomological studies have reported a substantial proportion of biting mosquitoes before midnight (34)(35)(36)(37). The under-ve may be protected against such risk as they would be at home and under bednets early.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in four sites under two unions (Kuhalong and Rajbila) in Bandarban district, Bangladesh (Additional file 1 : Fig. S1) [ 25 ]. The temperature in Bandarban district ranges from 13 °C in winter to 34.6 °C in summer.…”
Section: Methodsmentioning
confidence: 99%